Politik Hukum dalam Kebijakan Vaksinasi COVID-19 di Indonesia: Legal Policy in Indonesia’s COVID-19 Vaccination Policy - Ari Sudewo; C. Suryaarga Indrajaya; Euis Kurniawati; Hendi Fuky Lukmanta; Imas Rosidawati Wiradirja; Deny Haspada (SIYASI: Jurnal Trias Politica, 2025)
This study aims to examine the legal policy of the Indonesian government in determining the COVID-19 vaccination policy and the extent to which its implementation meets the principles of justice, especially in terms of equal access and an educational approach to the community. The research method used is a normative qualitative approach with an analysis of laws and regulations, official government documents, and scientific literature. Data were collected through literature studies and analyzed descriptively-analystically. The results of the study show that although the vaccination policy was designed as a form of protecting the public interest, its implementation still faces challenges in terms of inequality in vaccine distribution, lack of public education, and a legal approach that tends to be coercive. For this reason, the vaccination policy needs to be reviewed to emphasize the principles of social justice, respect for human rights, and public participation as part of a responsive and democratic legal policy.